The effect of cognitive behavioral therapy on the burden in drug dependent persons' caregivers: A randomized controlled clinical trial - Maryam Faghih; Saeid Pahlavanzadeh (Wolters Kluwer Medknow Publications, 2019)
Background: Drug dependence is one of the current problems that leads to the drug dependents persons' suffer and imposes a huge mental burden to their family members. This study aimed investigating to determine the effect of cognitive- behavioral therapy (CBT) on the burden of the caregivers of drug dependent people. In CBT, caregivers discover thought and behavioral mistakes and recover them. Materials and Methods: This randomized controlled clinical trial was conducted on 64 caregivers of drug dependent individuals referring to one of the clinical and educational centers in Isfahan, Iran, which were randomly assigned to two equal groups (intervention and control) in 2016. Intervention group under went eight 90-min CBT sessions, whereas control group attended 3 group sessions to express their experiences. Data were collected by Zarit Burden scale and the demographic questionnaire and analyzed by independent t-test, Chi-square, and ANCOVA repeated measure through SPSS 18. Results: Before the intervention, no statistical difference was observed among two groups in the mean scores of burden (t = 0.75,p= 0.46).There was a significant difference between three time points in the intervention group (F = 3.24, p < 0.001). However, care burden mean score did not show a significant reduction in the control group (F = 0.17,p= 0.96). Conclusions: The CBT can lead to reduction of burden in drug dependent caregivers'. We suggest encouraging nurses to establish educational programs such as CBT to maintain and improve caregiver's mental health.